PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Ivan S; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2022)
This study aims to examine the effect of corporate social responsibility (CSR) on financial performance. Corporate social responsibility is measured using the Corporate Social Responsibility Disclosure Index and financial performance is measured using ROA and ROE. This study uses a sample of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange during the 2016-2020 period. The number of pharmaceutical companies that were used as research samples were 7 companies for 5 years using purposive sampling method. This study uses secondary data from the annual financial statements of pharmaceutical companies for 2016- 2020. The results of the partial analysis show that the corporate social responsibility variable does not have a significant effect on financial performance as measured by ROA and ROE